Graphene oxide incorporated polyether sulfone nanocomposite antifouling ultrafiltration membranes with enhanced hydrophilicity. (1st July 2022) - Salim, Amber; Abbas, Muhammad Asad; Khan, Imran Ahmad; Khan, Muhammad Zafar; Javaid, Farhan; Mushtaq, Shehla; Batool, Mehwish; Yasir, Muhammad; Khan, Asim Laeeq; Khan, Asad U; Deen, Kashif Mairaj; Ahmad, Nasir M
Abstract: In this study, the polyether sulfone (PES) based membranes containing various concentrations of graphene oxide (GO), polyvinylpyrrolidone (PVP), and polyethylene glycol (PEG) were synthesized via the phase immersion method. This study aims to evaluate the effect of GO addition on the structural properties and performance of the membranes. The membranes were analyzed by x-ray diffraction (XRD), scanning electron microscopy (SEM), and Fourier transforms infrared spectroscopy (FTIR). The FTIR-ATR spectra indicated the presence of hydroxyl and carboxylic acid groups on the surface of GO-incorporated membranes, which improved their dispersion in the polymeric matrix and hydrophilicity. The SEM analysis of the GO-containing PES membranes confirmed the formation of a well-defined finger-like porous structure presenting adequate water flux (95 l.m –2 .h –1 ) and salt rejection (72%) compared to the pristine PES membranes (46 l.m –2 .h –1 and ∼35%, respectively). In addition, the significantly large wettability and considerably improved antibacterial characteristic (against S. aureus and E. coli strains ) of the GO-PES membranes are considered impressive features.